[Petőfi Literature Museum 1.]
1929-1936: Lajos Tihanyi and György Bölöni at a party, László Németh and Lőrinc Szabó at Zsigmond Móricz's home, Frigyes Karinthy on the street at winter, Dezső Kosztolányi at home